Assessing Customer Satisfaction of Halal Inspection Institutions Using Servqual-AHP for Halal Logistics Certification in Jabodetabek - Wynd Rizaldy; Prasadja Ricardianto; Sita Aniisah Sholihah; Bagus Sumargo; Nor Aida Abdul Rahman; Rizki Eri Utomo (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Halal logistics research in Indonesia is critical to ensure compliance with Islamic principles, enhance product safety and quality, and support business actors in the food, pharmaceutical, and manufacturing sectors to meet growing domestic and international demand. Currently, only 11% of logistics companies in Indonesia are halal-certified, indicating limited readiness to support halal supply chains by the end of 2024. High certification costs, complex procedures, and lengthy approval processes are key barriers.Purpose: This study develops a service quality analysis-analytical hierarchy process (SERVQUAL-AHP) model to strengthen halal policy and standardization in Halal Inspection Bodies (LPH) located in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (JABODETABEK) regions, in accordance with Law No. 33 of 2014 on Halal Product Assurance (JPH). aligning with Law No. 33 of 2014 on JPH.Design/methodology/approach:  Using a mixed-method approach with 77 logistics business actors and five experts. This study applies SERVQUAL, Importance Performance Analysis (IPA), and the AHP to identify service priorities and measure customer satisfaction using the Customer Satisfaction Index (CSI) at LPH.Findings/Result: The results highlight priority areas for service improvement and indicate a high level of customer satisfaction, suggesting strong potential to further enhance the service quality of LPH in the JABODETABEK regionConclusion: The study concludes that improving halal logistics certification To improve the quality of services at LPH, both responsiveness and assurance must be strengthened, particularly through secure digital systems and complete documentation. The findings also contribute theoretically by demonstrating the integration of SERVQUAL, IPA, AHP, and the CSI as a structured framework for evaluating and prioritizing service quality improvements in halal-certified services. Although the CSI is already high (CSI = 89%), the presence of SERVQUAL gaps is −0,19 indicates the need for continuous improvement to fully meet customer expectations.Originality/value (State of the art): Previous studies on halal logistics mainly focus on food products and general logistics performance, while research on the service quality of halal logistics certification is limited. This study fills this gap by developing an integrated SERVQUAL–AHP model to evaluate service quality, prioritize improvements, and measure the CSI in halal logistics certification services provided by LPH in Indonesia. Keywords: SERVQUAL, halal logistics, customer satisfaction, certification, complexity